This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution! +1! and problem too!
BONUS
n → ∞ lim n 1 ln ( n n n ! ( 2 n ) ! ) = n → ∞ lim n 1 ln ( n n 1 × n ! ( 2 n ) ! ) = n → ∞ lim n 1 ln ( n n n ! × n ! × n ! ( 2 n ) ! ) = n → ∞ lim n 1 ( ln ( n n n ! ) + ln ( n ! × n ! ( 2 n ) ! ) ) = n → ∞ lim n 1 ( ln ( n n n ! ) + ln ( ( 2 n n ) ) )
The n + 1 th central binomial coefficients is about 4 times the n th one, so...
n → ∞ lim n 1 ( ln ( n n n ! ) + ln ( 4 n ) ) = n → ∞ lim n 1 ( ln ( n n n ! ) + n ln ( 4 ) ) = n → ∞ lim n 1 ( ln ( n n n ! ) ) + ln 4
Now using stirling's,
n → ∞ lim n 1 ( ln ( n n ( e n ) n 2 π n ) ) + ln 4 = n → ∞ lim n 1 ( ln ( ( e 1 ) n 2 π n ) ) + ln 4 = n → ∞ lim n 1 ( − n + ln ( 2 π n ) ) + ln 4 = n → ∞ lim n 1 ( ln ( 2 π n ) ) + ln 4 − 1 = ln 4 − 1
Same way! (+1)
Great solution! (+1)
Is the answer for bonus question 2 ln 2 − 1 ?
This follows from Stirling’s approximation
n ! = 2 π n ( e n ) n
which can be re-written as
e 1 = ( n n n ! ) n 1 ( 2 π n ) − 2 n 1
And so the right factor on the right side drops out as n → ∞
Let's start by considering the following process.
n → ∞ lim ( n n n ! ) n 1 = n → ∞ lim ( n n n ! × n + 1 n + 1 ) n 1
n → ∞ lim ( n n n ! × n + 1 n + 1 ) n 1 = n → ∞ lim ( ( n + 1 ) n n ( n + 1 ) ! ) n 1
Let
n + 1 = N
Then
n → ∞ lim ( ( n + 1 ) n n ( n + 1 ) ! ) n 1 = N → ∞ lim ( N ( N − 1 ) N − 1 N ! ) n 1
N → ∞ lim ( N N ( 1 − N 1 ) N − 1 N ! ) n 1 = N → ∞ lim ( N N N ! × e ) n 1
Hence,
n → ∞ lim ( n n n ! ) n 1 = n → ∞ lim ( ( n + 1 ) n + 1 ( n + 1 ) ! × e ) n 1
And one can deduce that
n → ∞ lim ( n n n ! ) n 1 = n → ∞ lim ( ( n + k ) n + k ( n + k ) ! × e k ) n 1
Now, let k = n
n → ∞ lim ( n n n ! ) n 1 = n → ∞ lim ( ( n + n ) n + n ( n + n ) ! × e n ) n 1
n → ∞ lim ( ( 2 n ) 2 n ( 2 n ) ! × e n ) 2 n 2 = ⎝ ⎛ n → ∞ lim ( ( 2 n ) 2 n ( 2 n ) ! ) 2 n 1 × e 2 1 ⎠ ⎞ 2
Let the limit equal to L then,
⎝ ⎛ n → ∞ lim ( ( 2 n ) 2 n ( 2 n ) ! ) 2 n 1 × e 2 1 ⎠ ⎞ 2 = L 2 e = L
L = e 1
Problem Loading...
Note Loading...
Set Loading...
Let L = n → ∞ lim ( n n n ! ) 1 / n ⟹ ln L = n → ∞ lim n 1 ln ( n n n ! ) = n → ∞ lim n 1 ln ⎝ ⎜ ⎜ ⎜ ⎛ n times n ⋅ n ⋅ n ⋯ n n ⋅ ( n − 1 ) ⋅ ( n − 2 ) ⋯ 1 ⎠ ⎟ ⎟ ⎟ ⎞ = n → ∞ lim n 1 ln ( ( 1 ) ⋅ ( 1 − n 1 ) ⋅ ( 1 − n 2 ) ⋯ ( n 1 ) ) = n → ∞ lim n 1 ln ⎝ ⎛ r = 0 ∏ n − 1 ( 1 − n r ) ⎠ ⎞ = n → ∞ lim n 1 r = 0 ∑ n − 1 ln ( 1 − n r ) Applying Reimann Sums , ln L = ∫ 0 1 ln ( 1 − x ) d x = ∫ 0 1 ln x d x = − 1 ∴ L = e 1 ≈ 0 . 3 6 8
Bonus: n → ∞ lim n 1 ln ⎝ ⎛ n n n ! ( 2 n ) ! ⎠ ⎞